PENGARUH MODEL PEMBELAJARAN PBL BERBANTUAN MEDIA WORDWALL TERHADAP HASIL BELAJAR BAHASA INDONESIA KELAS III SDN RANDUGEDE - Fahmi fachruzaqi; Cerianing Putri Pratiwi; Candra Dewi (Universitas Negeri Medan, 2025)
This study aims to determine the effect of the Wordwall-assisted Problem Based Learning (PBL) model on the Indonesian language learning outcomes of third-grade students at SDN Randugede. The background of this study is based on students' low understanding of verb types due to less interactive learning. This study used a quasi-experimental method with a Nonequivalent Control Group Design. The sample consisted of two classes, namely the experimental class that used the PBL model assisted by Wordwall and the control class that used the conventional learning model. Data collection was carried out through descriptive tests (pretests and posttests), observations, interviews, and documentation. The results showed a significant difference between the learning outcomes of students in the experimental class and the control class. The average posttest scores of students in the experimental class were higher than those in the control class. This proves that the application of the PBL model assisted by Wordwall is effective in improving student learning outcomes, particularly in understanding types of verbs. Thus, this model can be used as an alternative interactive learning strategy that can improve students' understanding and motivation to learn at the elementary school level.